Terminology of Kinship in Malecu: Its Documentation and its Obsolescence - Sánchez Avendaño, Carlos (2023)
In this article data on documentation and obsolescence of the kinship lexical system in Malecu are analyzed. The historical and professional documentation are comparativedly examined in detail, in order to describe, in the context of the advanced desplacement of the Malecu language, the individual lexical systems of current speakers with distinct manifestations of linguistic and communicative competence.